2019
DOI: 10.3389/fonc.2019.00732
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Stereotactic Body Radiation Therapy for Treatment of Adrenal Gland Metastases

Abstract: Purpose: This study aimed to describe our institutional experience in the use of stereotactic body radiation therapy (SBRT) for the management of adrenal gland metastases from multiple primary cancers. Materials and Methods: We retrospectively reviewed 31 patients who underwent SBRT as treatment for 33 adrenal gland lesions in the academic radiotherapy department of Oscar Lambret cancer center between May 2011 and September 2018. The primary study endpoints were 1- and 2-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In line with these results, another analysis demonstrated that adrenal SBRT with a BED 10 ≥ 85.5 Gy correlated with superior LC [41]. Notably, the patients in the study by Scouarnec et al were treated with higher total doses in BED 10 (median 112.5 Gy) compared to the median BED 10 in our analysis (75.0 Gy), which might also have impaired our results [40]. We also detected a non-significant trend for superior LC if a BED 10 ≥ 75.0 Gy was applied (p = 0.101), both patients diagnosed with a local recurrence were treated with a BED 10 < 67.5 Gy.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In line with these results, another analysis demonstrated that adrenal SBRT with a BED 10 ≥ 85.5 Gy correlated with superior LC [41]. Notably, the patients in the study by Scouarnec et al were treated with higher total doses in BED 10 (median 112.5 Gy) compared to the median BED 10 in our analysis (75.0 Gy), which might also have impaired our results [40]. We also detected a non-significant trend for superior LC if a BED 10 ≥ 75.0 Gy was applied (p = 0.101), both patients diagnosed with a local recurrence were treated with a BED 10 < 67.5 Gy.…”
Section: Discussionsupporting
confidence: 70%
“…Haidenberger et al analyzed robotic radiosurgery using active tumor tracking at the CyberKnife for adrenal SBRT and reported much smaller PTV sizes of in median 48.6 cm 3 compared to the median PTV size of 95.9 cm 3 in our study, in which an ITV-based approach was applied [43]. Due to the smaller PTV sizes and hence the larger distance to surrounding radiosensitive OARs, higher doses potentially leading to superior LC could be delivered when active motion management strategies are used [40,46]. However, as gating and tracking technologies are usually applied in combination with X-ray based image-guidance, the invasive implantation of fiducial markers in the well vascularized adrenal glands becomes necessary.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…There is sparse literature considering the adrenal glands as organs at risk in RT. The evaluation of toxicity pro les was mostly from SBRT for adrenal metastases [31][32][33]. We regarded healthy adrenal glands, but not metastatic ones, as essential organs to spare in RT planning, which differed from previous studies.…”
Section: Discussionmentioning
confidence: 99%